Estimación del índice de mérito genético total del programa de mejoramiento genético sostenible de bovinos de leche en la provincia de Cotopaxi, cantón Pujilí de la parroquia La Victoria - Cuyo Villacís, Jenifer Alexandra (2023)
In the province of Cotopaxi, canton Pujilí, parish La Victoria, the inadequate management of most of the small milk producers together with the lack of knowledge of adequate food supplementation and nutrition make that their animals do not provide a profitable production, so it is necessary to implement a genetic improvement program in order to determine the total genetic merit index. We worked with 16 producers from which we obtained 33 animals and only 6 cattle with milk production. We began by collecting data on the weight of the animals, measuring the density of the milk and its production in liters for each of the cows, and at the same time we applied a sanitary calendar in order to guarantee optimum production. The average production cost per liter of milk in the parish was $0.18. The cost of sale was $0.48. This resulted in an average monthly profit of $112.38 per farm. Approximately 44% of the cost of production represents feed, followed by veterinary services (18%), basic services (23%) and other expenses (15%). Therefore, it was determined that the Genetic Merit index for the parish should include daily weight gain, milk production and density. The average daily weight gain is 223.68 gr, the animal with the highest daily weight gain was the Colorada cow with 273.21 gr of the owner Maria Chiluisa, the average milk production is 2165.57 kg of milk per year, The animal with the highest milk production was the Ojo Pintado cow with 1901.43 kg of the owner Carmen Jiménez and with respect to milk density there is an average of 1.017 gr/ml, the best animal with the highest milk density was the María cow with 1.022 gr/ml of the owner Carmen Jiménez. A monthly average of 3060 liters per lactation was obtained. Thanks to the analysis of the phenotypes, we were able to estimate the response to selection. With respect to daily weight gain, it is estimated that the objective of genetic improvement will be reached in the second generation, since it showed values of 423.21 grams of daily weight gain, In milk production, the objective would be reached in the second generation since it shows values of 4067.69 kg of milk per year and finally, milk density, the objective of improvement will be obtained in the first generation since it is similar to the desired values and is 1.022 gr/ml of milk in the response to the selection.